Formation of Criteria of Assessment of Infrastructure Projects of Sea Ports Development - Logutova Tamara G.; Demyanchenko Alisa G. (Bìznes Inform, 2014)
The spectrum of criteria, by which assessment of tender offers of projects of state-private partnership in the port industry is carried out, includes a small but capacious set of indicators of financial and economic efficiency and qualification level of contenders. However, the study of foreign methods of assessment of projects in sea ports and domestic experience of carrying out tenders in other industries shows that a more clear division of assessment of both tender offers and contenders is rational. The article uses some methods and approaches to scientific study – generalisation, systematisation and analysis of foreign and domestic experience of carrying out tenders and acts of law. In the result the article forms a scheme of assessment of tender offers and investors and also offers an algorithm of calculation of the integral tender assessment, based on division of tender criteria by four groups: technical and economic, financial (for a tender offer), financial and investment, and organisational (for investors). The offered aspects of improvement of methods of tender selection of projects, realised in the port industry with the help of the mechanism of state-private partnership, would facilitate a more balanced and optimal selection of the best offer not only from the point of view of its content, but also the characteristic of the investor that proposes it. On the other hand, the use of the common, successfully tested under different conditions of project realisation, numerical method of assessment would be the guarantee of applicability of the of the proposed measures.